Ambidextrous pedagogical leadership and educational quality in the Postgraduate Unit of the UNMSM Faculty of Education in times of the COVID-19 pandemic, 2020 - Condezo Tascca , Sailor Marino (2024)
The objective of this research is to identify and establish the relationship that exists between ambidextrous pedagogical leadership and educational quality in the Graduate Unit of the Faculty of Education of the Universidad Nacional Mayor de San Marcos (UNMSM) in Lima. To do this, we use a quantitative approach, cross-sectional and ordinal level, hypothetical deductive method. The sample was made up of 120 persons. To collect information, two questionnaires were used, the validity of which was determined by the judgment of three experts and the reliability using the Cronbach's Alpha statistician. The results were analysed by descriptive statistics and the evaluation between both variables was measured by inferential statistics through Spearman's Rho statistician. After the analysis, the compensation coefficient Spearman's Rho = 0.729**, which is interpreted as a very good compensation, it was also obtained that the value of p = 0.000 (p < 0.05); Therefore, the null hypothesis is rejected and it is accepted that there is a relationship between ambidextrous pedagogical leadership and educational quality in the graduate unit of the UNMSM faculty of education in times of the covid-19 pandemic, 2020.